185 The Impacts of Commercial Dietary Acidifiers on Growth Performance of Nursery Pigs - Dahmer, Payton L (J Anim Sci, 2021)
A total of 360 weanling pigs (DNA 200 x 400; initially 9.7 ± 0.23 kg BW) were used in a 21-d growth trial to evaluate the effects of commercial diet acidifiers in nursery diets. Upon weaning, pigs were weighed and allotted to pens (6 pigs/pen, 10 replicate pens/treatment, blocked by 2 separate nursery rooms) and pens were then randomly assigned to one of 6 treatment diets: 1) negative control (no antibiotics or acidifiers) and the control with 2) 0.25% Acidifier A (KEM-GEST™, Kemin Industries, Des Moines, IA); 3) 0.3% Acidifier B (ACITVATE® DA, Novus International, Saint Charles, MO); 4) 0.5% Acidifier C (OutPace®, PMI Additives, Arden Hills, MN); 5) 50 g/ton carbadox; 6) 400 g/ton chlortetracycline. Pigs were fed common phase 1 and phase 2 starter diets without antimicrobials for 21 days, then fed experimental diets for 21 days. Data were analyzed as a completely randomized block design with pen as the experimental unit. Dietary treatment significantly impacted (P < 0.05) all growth response criteria for each week of the experiment. Overall (d 0 to 21), ADG was the greatest (P < 0.0001) for pigs fed a diet containing CTC. Likewise, ADFI was increased (P < 0.0001) for pigs consuming CTC compared to those fed the negative control, acidifier A, acidifier B and carbadox diets, while those fed acidifier C were intermediate. Feed efficiency was poorest (P < 0.0001) in pigs fed a diet with carbadox. By the end of the experiment, pigs fed CTC were significantly heavier (P < 0.0001) than pigs fed all remaining treatments. In summary, feeding CTC improved nursery pig performance while carbadox unexpectedly reduced it. The addition of dietary acidifiers did not improve growth performance compared to a negative control. [Image: see text]